Respuesta :
Answer:
B
Step-by-step explanation:
f(x) = [tex]x^{2} -8x+3[/tex]
=> f(x)= [tex]x^{2} -2(x)(4)+4^{2}-4^{2}+3[/tex]
=> f(x) = [tex](x-4)^{2}-4^{2}+3[/tex]
=> f(x) = [tex](x-4)^{2}-16+3[/tex]
=> f(x) = [tex](x-4)^{2}-13[/tex]
Answer:
f(x) = (x - 4)² - 13
Step-by-step explanation:
f(x) = x² − 8x + 3
x² − 8x + 3 = 0
x² - 8x = -3
x² - 8x + 4² = -3 + 4²
x² - 8x + 4² = -3 + 16
x² - 8x + 4² = 13
(x - 4)² = 13
(x - 4)² - 13 = 0
The vertex form of a quadriatic function f(x) = x2 − 8x + 3 is;
f(x) = (x - 4)² - 13